Seismisitas Pulau Sumatera dan Wilayah Sekitarnya Akibat Aktivitas Seismo-Tektonik Zona Subduksi dan Patahan - Choirunnisa, Kayla; Fahmi, Muhammad Nurul; Realita, Arie (Inovasi Fisika Indonesia, 2025)
This study aims to analyze the seismicity of Sumatra Island and its surrounding areas, which are known for their intense seismic activity due to complex geological and tectonic conditions. The analysis was conducted using the frequency–magnitude distribution (FMD) to estimate three seismic parameters: Mc, b-value, and a-value. Earthquake data were obtained from the ISC–GEM catalog (1924–2024) with a magnitude range of 4.0 ≤ Mw ≤ 9.5 and processed using ZMAP7.0 in Matlab2018a. Earthquake source depths were classified into shallow and intermediate sources. The analysis results show a dominance of shallow earthquakes, with higher a-values in the western zones (highest in Zone 3: 6.02), indicating intense seismic activity. In contrast, the eastern zones exhibit lower a-values and more stable seismic behavior. The b-values range from 0.4 to 0.9, reflecting high tectonic stress across the study area. Low b-values in the western zones suggest significant seismic energy accumulation and potential for large future earthquakes. The relationship among Mc, b, and a illustrates the characteristics of earthquake sources and supports probabilistic modeling and microzonation prioritization in vulnerable regions.